The Influence of Online Games Against the Development of Student Cadre of the Faculty of Education, Makassar State University - Muh Nur Ikhsan Hidayat (International Consortium of Education and Culture Research Studies, 2020)
Today's development has created a communication tool that is truly sophisticated that can be used to play games anywhere, what more can facilitate many groups in carrying out activities especially students in academic or non-academic activities (Student Affairs). But of course there are negative impacts on the game itself can specifically interfere with psychological, cognitive, and less productive activities when consuming excessive games.